Comparative effectiveness of subcutaneous tocilizumab versus intravenous tocilizumab in a pan-European collaboration of registries. Issue 2 (5th November 2018) - Lauper, Kim; Mongin, Denis; Iannone, Florenzo; Klami Kristianslund, Eirik; Kvien, Tore K; Nordström, Dan; Pavelka, Karel; Pombo-Suarez, Manuel; Rotar, Ziga; Santos, Maria Jose; Codreanu, Catalin; Lukina, Galina; et al.
Abstract : Objective: To compare the real-word effectiveness of subcutaneous tocilizumab (TCZ-SC) and intravenous tocilizumab (TCZ-IV) in rheumatoid arthritis (RA). Methods: Patients with RA with TCZ from eight European registries were included. Drug retention was compared using unadjusted Kaplan-Meier and Cox models adjusted for baseline patient, disease and treatment characteristics, using a strata term for year of treatment initiation and country of registry. The proportions of patients achieving Clinical Disease Activity Index (CDAI) remission and low disease activity (LDA) at 1 year were compared using samples matched on the same covariates and corrected for attrition using LUNDEX. Results: 3448 patients were retrieved, 2414 with TCZ-IV and 1034 with TCZ-SC. Crude median retention was 3.52 years (95% CI 3.22 to 3.85) for TCZ-IV and 2.12 years for TCZ-SC (95% CI 1.88 to 2.38). In a country-stratified and year of treatment initiation–stratified, covariate-adjusted analysis, hazards of discontinuation were similar between TCZ-SC and TCZ-IV treated patients (HR 0.93, 95% CI 0.80 to 1.09). The average adjusted CDAI change at 1 year was similar in both groups (−6.08). After matching, with 560 patients in each group, CDAI remission corrected for attrition at 1 year was also similar between TCZ-SC and TCZ-IV (10.4% in TCZ-IV vs 12.8% in TCZ-SC (difference: 2.4%, bootstrap 95% CI −2.1% to 7.6%)), but CDAI LDA was lower in TCZ-IV patients: 41.0% in TCZ-IV versus 49.1% in TCZ-SC (difference: 8.0 %; bootstrap 95% CI 2.4% to 12.4%). Conclusion: With similar retention and effectiveness, TCZ-SC is an adequate alternative to TCZ-IV for RA. When possible, considering the costs of the TCZ-IV route, TCZ-SC should be the preferred mode of administration.